Responsive charge transport in wide-band-gap oxide films of nanostructured amorphous alkali-gallium-germanosilicate. Issue 25 (5th June 2019) - Remondina, J.; Paleari, A.; Golubev, N. V.; Ignat'eva, E. S.; Sigaev, V. N.; Acciarri, M.; Trabattoni, S.; Sassella, A.; Lorenzi, R.
Abstract : Ga-Oxide nano-segregation in alkali-germanosilicate amorphous films gives rise to a responsive material with nonlinear electric conduction and hysteretic charging mechanisms. Abstract : The demand for new responsive materials is continuously growing in several areas as a result of approaching the physical limits of technologies, which now calls for a drastic change of strategy. Here, we report on memory responsive oxide-in-oxide nanostructured films obtained by radio-frequency sputtering of a 7.5Li2 O–2.5Na2 O–20Ga2 O3 –45GeO2 –25SiO2 (mol%) glass target produced by melt quenching. Atomic force microscopy and scanning electron microscopy show that as-deposited oxide layers exhibit native nanophase separation, with the occurrence of Ga-rich oxide nanostructures – about 15 nm thick and 100 nm in diameter – incorporated in oxide layers about 70 nm thick. Interestingly, despite the wide band gap (above 4 eV), the nanostructured oxide films reveal the formation of unconventional electric field dependent charge transport paths across the material. The frequency and temperature dependence of electric conductivity and dielectric function highlights n-type conduction sustained by charge percolation through the oxide layer. Importantly, the results demonstrate the occurrence of conductivity changes by more than an order of magnitude in a few volts, and trapped charge values up to 10 16 electrons per cm 3 .